A comparative analysis of differentially expressed mRNAs, miRNAs and circRNAs provides insights into the key genes involved in the high-altitude adaptation of yaks - Qianyun Ge; Yongbo Guo; Wangshan Zheng; Yuan Cai; Xuebin Qi; Shengguo Zhao (BMC Genomics, 2021)
Abstract Background Yaks that inhabit the Tibetan Plateau exhibit striking phenotypic and physiological differences from cattle and have adapted well to the extreme conditions on the plateau. However, the mechanisms used by these animals for the regulation of gene expression at high altitude are not fully understood. Results Here, we sequenced nine lung transcriptomes of yaks at altitudes of 3400, 4200 and 5000 m, and low-altitude Zaosheng cattle, which is a closely related species, served as controls. The analysis identified 21,764 mRNAs, 1377 circRNAs and 1209 miRNAs. By comparing yaks and cattle, 4975 mRNAs, 252 circRNAs and 75 miRNAs were identified differentially expressed. By comparing yaks at different altitudes, we identified 756 mRNAs, 64 circRNAs and 83 miRNAs that were differentially expressed (fold change ≥2 and P-value < 0.05). The pathways enriched in the mRNAs, circRNAs and miRNAs identified from the comparison of yaks and cattle were mainly associated with metabolism, including ‘glycosaminoglycan degradation’, ‘pentose and glucuronate interconversions’ and ‘flavone and flavonol biosynthesis’, and the mRNAs, circRNAs and miRNAs identified from the comparison of yaks at different altitude gradients were significantly enriched in metabolic pathways and immune and genetic information processing pathways. The core RNAs were identified from the mRNA-miRNA-circRNA networks constructed using the predominant differentially expressed RNAs. The core genes specific to the difference between yaks and cattle were associated with the endoplasmic reticulum and fat deposition, but those identified from the comparison among yaks at different altitude gradients were associated with maintenance of the normal biological functions of cells. Conclusions This study enhances our understanding of the molecular mechanisms involved in hypoxic adaptation in yaks and might contribute to improvements in the understanding and prevention of hypoxia-related diseases.